Compensation Policy Implementation Of Fuel Oil, In The District Konawe, Southeast Sulawesi Province (Study on Implementation of Direct Cash Assistance) - Malik MALIK; Noning Verawati (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
This study titled Compensation Policy Implementation Fuel Particularly Direct Cash Assistance in Konawe, Southeast Sulawesi Province. This research uses descriptive method with qualitative approach, which starts from the initial informant, and data that is not provided by the initial informant, hereinafter through the second informant and rolling on until sufficient data required. Data acquisition is done through informal and unstructured interviews using the interview guide as a handle.Based on the results of the study showed that, (1) the communication factor in implementation was less socialized; (2) Disposition factor or attitude implementor basically not shown seriousness in implementing services to poor families; (3) Human Resources readiness factor (executor) in carrying out policy is not optimal; (4) Factor bureaucratic structure / organization implementing compensation Fuel particular direct cash assistance was not implemented according to operational standards, so the chance of overlapping duties and authority between sectors.Based on the results of research and discussion, it can be argued that the findings from this study is that the compensation policy implementation Fuel Particularly Direct Cash Assistance, the most influencing factor is the communication of local communities in this regard is the language of the region in the implementation of policies, both between and among executive officers of the local poor.